2020
DOI: 10.1172/jci130728
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus toxin suppresses antigen-specific T cell responses

Abstract: Authorship note: BL and RO contributed equally to this work. Conflict of interest: JBW has a financial agreement with Aridis Pharmaceuticals related to patents owned by the University of Chicago (US patent application 12/675,597, entitled "Methods and compositions related to immunizing against staphylococcal lung diseases and conditions").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
8
25
0
Order By: Relevance
“…In comparison with wild-type S. aureus , infection with a Hla deletion mutant resulted in greater expansion of antigen- specific memory T cells. Interestingly, maternal immunization with Hla resulted in enhanced development of memory T cells in pups following post-natal infection, supporting the idea that early exposure to Hla interferes with the development of immunological memory ( 35 ). Bonifacius et al have recently reported that Hla induced direct death of Th1-polarized cells, while Th17 cells were relatively resistant.…”
Section: Expansion Of Naïve To Memory and Effector T Cells In mentioning
confidence: 52%
See 3 more Smart Citations
“…In comparison with wild-type S. aureus , infection with a Hla deletion mutant resulted in greater expansion of antigen- specific memory T cells. Interestingly, maternal immunization with Hla resulted in enhanced development of memory T cells in pups following post-natal infection, supporting the idea that early exposure to Hla interferes with the development of immunological memory ( 35 ). Bonifacius et al have recently reported that Hla induced direct death of Th1-polarized cells, while Th17 cells were relatively resistant.…”
Section: Expansion Of Naïve To Memory and Effector T Cells In mentioning
confidence: 52%
“…Therefore, similar to the bicomponent leukotoxins, Hla expression can disrupt antigen presentation to T cells by directly killing APCs and by inhibiting differentiation of T cells to effector and memory cells ( 34 ). Primary infection in C57BL/6 mice with Hla-producing S. aureus impaired protection against recurrent infection ( 35 ). This was attributed, at least in part, to direct toxicity of Hla to dendritic cells, whose numbers were decreased following skin infection with wild type S. aureus , but not an Hla mutant ( 35 ).…”
Section: S Aureus and Antigen Presenting Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…During infections, neutrophils, monocytes, macrophages, dendritic cells, and memory T cells are thought to be targeted by the leukocidins ( Spaan et al, 2017 ). A close relative of the bicomponent leukocidins, α-toxin, also exhibits leukocidal activity and was recently shown to suppress antigen-specific T cell responses ( Lee et al, 2020 ). Although these toxins suppress host adaptive immunity against S. aureus, exposure to these virulence factors during the initial infection is crucial for the development of neutralizing antibodies ( Zhao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%